Penerapan Strategi Segmenting, Targeting, Positioning Dalam Meningkatkan Nilai Kualitas Produk Tabungan Prima iB Bank Tabungan Negara Syariah Kcps Probolinggo - halim, halima halima; Islam, Muhammad Hifdil; Nasrifah, Maula (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2024)
Abstrak: This research aims to find out how segmenting, targeting and positioning (STP) strategies are implemented in a company. This method uses qualitative methods in collecting primary data and secondary data. Primary data was obtained using data collection techniques through interviews (In-depth interviews), focus group discussions. Meanwhile, secondary data was obtained such as books, notes and theses, scientific journals relating to the research focus. The results of this research show that bank BTN Syariah Kcps Probolinggo implements the STP strategy to improve the quality of the Prima iB Savings product. Product quality value is measured in terms of performance, features, reliability, aesthetics, applicability, durability, maintenance and perceived quality especially by using the STP strategy to reach the wider community more easily. This research is also equipped with the obstacles and solutions to solving existing problems at the Prima iB Bank BTN Syariah Kcps Probolinggo Savings company. Keywords ; STP Strategy, Product Quality, Prima iB Savings.